General Approaches to Internet of Things: Internet of Things in Information Management - Yalçınkaya, Bahattin; Cibaroğlu, Mehmet Oytun ([TR] Türk Arşivciler Derneği, 2019)
The continuous development of information and communication Technologies (ICT) enables the emergence of new technologies at an increasing rate. One of these technologies is the Internet of Things (IoT) concept, in which devices can communicate with each other and produce data or information. IoT, which can be defined basically as a network in which physical objects can communicate with each other or with larger systems, has deeply influenced data, information and knowledge management processes along with new generation technologies. In this study, IoT is examined as history, knowledge management, problems and requirements in the context of literature review and the most up-to-date information has been given about IoT implementations both in our country and the world. As a result, it is seen that there have been various problems about the IoT especially such as security and privacy concerns and related studies have been examined to address these problems. The most important objective of the study is to have an idea about IoT and to promote the studies in this field especially in academic sense in our country by introducing application phases.

Bilgi ve iletişim teknolojilerinin sürekli gelişmesi, yeni teknolojilerin de artan bir hızda ortaya çıkmasını sağlamaktadır. Bu teknolojilerden bir tanesi de cihazların birbirleri ile iletişim kurabildiği, veri veya enformasyon üreten Nesnelerin İnterneti (Nİ) kavramıdır. Temel olarak fiziksel nesnelerin birbirleriyle veya daha büyük sistemlerle bir bağlantı oluşturarak iletişim kurabildiği bir ağ olarak tanımlanabilecek Nİ, yeni nesil teknolojiler ile birlikte veri, enformasyon ve bilgi yönetim süreçlerini derinden etkilemiştir. Bu çalışmada Nİ; tarihçesi, bilgi yönetimi bağlamında, problemleri ve gereklilikleri bağlamında literatür taraması yapılarak incelenmiş; ülkemizde ve dünyada gerçekleştirilen Nİ uygulamaları hakkında en güncel bilgiler verilmiştir. Çalışma sonucunda; Nİ kavramı hakkında güvenlik ve gizlilik endişeleri başta olmak üzere çeşitli sorunlar olduğu görülmüş, bu sorunların giderilmesi adına yapılan çalışmalar incelenmiştir. Çalışmanın en önemli hedefi; Nİ hakkında bilgi sahibi olmak ve uygulama alanlarının tanıtılarak ülkemizde de özellikle akademik anlamda bu alandaki çalışmaları teşvik etmektir.
Nesnelerin İnternetine Genel Yaklaşımlar: Bilgi Yönetiminde Nesnelerin İnterneti